Hsp20-Engineered Mesenchymal Stem Cells Are Resistant to Oxidative Stress via Enhanced Activation of Akt and Increased Secretion of Growth Factors - Wang, Xiaohong (2009)
Although heat-shock preconditioning has been shown to promote cell survival under oxidative stress, the nature of heat-shock response from different cells is variable and complex. Therefore, it remains unclear whether mesenchymal stem cells (MSCs) modified with a single heat-shock protein (Hsp) gene are effective in the repair of a damaged heart. In this study, we genetically engineered rat MSCs with Hsp20 gene (Hsp20-MSCs) and examined cell survival, revascularization, and functional improvement in rat left anterior descending ligation (LAD) model via intracardial injection. We observed that overexpression of Hsp20 protected MSCs against cell death triggered by oxidative stress in vitro. The survival of Hsp20-MSCs was increased by approximately twofold by day 4 after transplantation into the infarcted heart, compared with that of vector-MSCs. Furthermore, Hsp20-MSCs improved cardiac function of infarcted myocardium as compared with vector-MSCs, accompanied by reduction of fibrosis and increase in the vascular density. The mechanisms contributing to the beneficial effects of Hsp20 were associated with enhanced Akt activation and increased secretion of growth factors (VEGF, FGF-2, and IGF-1). The paracrine action of Hsp20-MSCs was further validated in vitro by cocultured adult rat cardiomyocytes with a stress-conditioned medium from Hsp20-MSCs. Taken together, these data support the premise that genetic modification of MSCs before transplantation could be salutary for treating myocardial infarction.